(untitled) (World Bulletin of Social Sciences, 2023)
Today, in order to raise the morale of young people, a more effective organization of social activities and an analysis of their activities based on new criteria are required. One of the requirements of our time was the formation of a new structure of the self-government body that meets the requirements of the time, the effective organization of its administrative system